An Analysis on the Translation Transcript of 'Rico the Series: My Father is My Hero and Special Gift' - Elsa Nadia Maharani (Jurnal Vokasia, 2023)
Riko The Series is an Educational animated children's series and presents scientific content related to the Qur’an (Quranic Sciences) in each episode. The purposes of this study are to translate the transcript of an animated short film entitled “My Father Is My Heroand Special Gift”, to explain the translation process, techniques, obstacles, and solutions. The method used in translating Animated Short Film Riko the Series is literature study and direct practice. The translation of this short film “Riko the Series” consists of several steps, they were analyzing the short film Riko the Series, transferring the message from the source language to the target language, restructuring the message contained in the source language, and evaluating the results of the translation. The translation techniques used in this study were amplification, variation, transposition, borrowing, and literal translation.During the direct practice, the obstacles faced were the lack of vocabulary, the difficulty in finding the right diction, and the difficulty in equating the accuracy of subtitles with the timeliness of film dialogue. To overcome the obstacles the solutions were looking for terms in the target language from words that are not understood with the help of a dictionary, and learning the features contained in the Aegisub application.